A lower bound on the number of mechanisms for discriminating fourth and higher order spatial correlations - Seamons, John W.G.; Barbosa, Marconi S.; Bubna-Litic, Anton; Maddess, Ted (Vision research (Oxford), 2015)
•We evaluated complex texture discrimination using 27 isotrigon textures.•About 3 mechanisms may drive of sense of complex image structure.•There was limited evidence of improved discrimination by learning. Research on single striate cortical neurons has often concentrated on their responses to stimuli defined by two-point correlations. Texture discrimination studies using a relatively small palette of isotrigon textures have indicated that we are sensitive to third and higher-order spatial correlations. To further evaluate the underlying mechanisms of texture discrimination subjects discriminated random binary noise patterns from ten new isotrigon texture types. Factor analysis revealed that as few as three mechanisms may govern the detection of fourth and higher order image structure. This supports the findings of previous studies using different isotrigon textures. The computation of higher-order correlations by the brain is neurophysiologically plausible. The mechanisms identified in this study may represent some short range nonlinear combination of recursive and/or rectifying processes.